New insight into teratogenic effects of (S)-thalidomide in zebrafish embryos growing inside the chorion and subjected to electric pulses - Anna Małkowska; Łukasz Szymański; Julita Nowakowska; Dorota Kaczorek; Agnieszka Nosal-Wiercińska; Robert Kawęcki; Ireneusz P. Grudzinski; Anna M. Nowicka (Scientific Reports)
Abstract Studies of (S)-thalidomide were conducted on zebrafish embryos subjected to electroporation processes using a square wave pulse generator. The results showed that the electroporation increases the absorption of (S)-thalidomide through the chorion into the growing embryos, which was confirmed by increased thalidomide levels in the embryo bodies at different hours post-treatments using differential pulse voltammetry and controlled-growth mercury drop electrode techniques. (S)-thalidomide administered by electroporation produced structural body deformations in zebrafish embryos as showed by scanning electron microscopy studies. Detailed transmission electron microscopy analysis evidenced multiple deposits of the outer layer and translucencies in the chorion structure, which was also pronounced on the mitochondrial membranes. The results confirmed the spontaneous conversion of the (S)-thalidomide enantiomer to the (R)-enantiomer in embryos exposed to the (S)-thalidomide only and subjected to electroporation pulses. The electroporation was found as a promising method to increase the uptake of (S)-thalidomide in the developmental studies on early zebrafish embryos growing in the chorion.